OPTIMALISASI KHUTBAH JUMAT SEBAGAI METODE DAKWAH DALAM MENDIDIK MASYARAKAT - Suriati Suriati (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2012)
Friday prayer is one of the Muslims' obligations carried out once a week on Friday. Friday sermon is a speech or lecture that contains adminition and guidance. This sermon is delivered by the khatib (precher) meeting the requirements determinated by shariah to convey Islamic teachings to the audience on a particular theme. Friday sermon has a strategic meaning and function because it is loaded with religious values delivered to the congregation. In addition, the Muslims gathered in mosques in a large number. From this, a khatib need to optimize precious moment to preach Islamic massages to the people through this sermon to that the congregation can recieve and understand the content of the Friday sermon delivered.